2020
DOI: 10.2147/ijwh.s238460
|View full text |Cite
|
Sign up to set email alerts
|

<p>Quality of Life in Japanese Patients with Dysmenorrhea Treated with Ethinylestradiol 20 μg/Drospirenone 3 mg in a Real-World Setting: An Observational Study</p>

Abstract: Background: Dysmenorrhea affects approximately 80% of women in Japan and has a negative impact on health-related quality of life (HRQoL). Low-dose estrogen/progestin combined oral contraceptives have been shown to reduce the severity of dysmenorrhea symptoms. This study characterized HRQoL in Japanese women with dysmenorrhea before and after ethinylestradiol/drospirenone (EE/DRSP) treatment. Methods: This prospective, observational study recruited 531 patients, of which 186 were evaluated after treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…The results of this analysis are consistent with those of a previous real-world study of the cyclic regimen of EE/DRSP, which showed that 6–8 cycles of treatment had a positive impact on HRQL in Japanese women with dysmenorrhea ( n = 186), as assessed using the 36-Item Short-Form Health Survey [ 27 ]. Similar results have also been observed in recent studies (including prospective clinical trials) with other hormonal treatments; improvements in HRQL in patients with endometriosis-associated pain or dysmenorrhea have been demonstrated with pharmacotherapies such as combined oral contraceptives, gonadotropin-releasing hormone receptor antagonists, and subdermal implant and oral formulations of progestin [ 36 40 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of this analysis are consistent with those of a previous real-world study of the cyclic regimen of EE/DRSP, which showed that 6–8 cycles of treatment had a positive impact on HRQL in Japanese women with dysmenorrhea ( n = 186), as assessed using the 36-Item Short-Form Health Survey [ 27 ]. Similar results have also been observed in recent studies (including prospective clinical trials) with other hormonal treatments; improvements in HRQL in patients with endometriosis-associated pain or dysmenorrhea have been demonstrated with pharmacotherapies such as combined oral contraceptives, gonadotropin-releasing hormone receptor antagonists, and subdermal implant and oral formulations of progestin [ 36 40 ].…”
Section: Discussionsupporting
confidence: 88%
“…Clinical studies in Japanese women have demonstrated that the cyclic regimen of EE/DRSP improved HRQL outcomes associated with dysmenorrhea [ 27 ], the cyclic and extended regimens reduced dysmenorrhea-related pain [ 25 , 28 ], and the extended regimen improved endometriosis-related pain [ 29 ]. However, the impact of the extended regimen of EE/DRSP on HRQL in patients with dysmenorrhea or endometriosis-associated pain in a real-world setting has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies have investigated the impact of dysmenorrhea on HRQL, only one publication investigated the benefits of taking LEP in Japan [ 17 ]. A patient-reported outcome study of Japanese women with dysmenorrhea treated with ethinylestradiol/drospirenone (EE/DRSP) showed HRQL improvements, as measured by the 36-Item Short-Form Health Survey version 2.0 (SF-36v2.0) [ 17 ]. However, studies investigating the impact of cyclic or extended LEP regimens on HRQL or examining the relationship between HRQL and work productivity in Japanese women are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…An improvement in total MDQ scores was observed in both the premenstrual and menstrual periods, meaning that the LNG-IUS may improve various symptoms before and during menstruation. The onset of primary dysmenorrhea usually occurs on the first day of menstruation; the severity is generally higher during the initial 24–48 h [ 34 ]. This may explain why the total MDQ score at baseline in our study tended to be higher during the menstrual period than the premenstrual period.…”
Section: Discussionmentioning
confidence: 99%